PENGARUH PENERAPAN E-COMMERCE, FINANCIAL LITERACY DAN PERAN SUMBER DAYA MANUSIA (SDM) TERHADAP KINERJA USAHA MIKRO, KECIL, DAN MENENGAH (UMKM) DI KECAMATAN DEPOK, KABUPATEN SLEMAN, PROVINSI DAERAH ISTIMEWAH YOGYAKARTA: PENGARUH PENERAPAN E-COMMERCE, FINANCIAL LITERACY DAN PERAN SUMBER DAYA MANUSIA (SDM) TERHADAP KINERJA USAHA MIKRO, KECIL, DAN MENENGAH (UMKM) DI KECAMATAN DEPOK, KABUPATEN SLEMAN, PROVINSI DAERAH ISTIMEWAH YOGYAKARTA - Lapodo, Asyri; As’Ari, Hasim (ITB AAS Indonesia Surakarta, 2025)
This study aims to analyze the influence of E-Commerce Implementation, Financial Literacy, and the Role of Human Resources (HR) on the Performance of Micro, Small, and Medium Enterprises (MSMEs) in Depok District, Sleman Regency, Special Region of Yogyakarta. The research uses a quantitative approach with multiple linear regression analysis. Primary data were collected through questionnaires distributed to 100 MSME owners, selected using a purposive sampling method. The research instruments were tested using validity and reliability tests, and data analysis was conducted through classical assumption tests, t-tests, and regression analysis.The results show that the E-Commerce variable has no significant effect on MSME performance, indicating that business owners still lack sufficient understanding of digital technology utilization. Meanwhile, the Financial Literacy variable has a positive and significant effect on MSME performance, meaning that higher financial literacy levels lead to better business performance. The Human Resources (HR) variable shows a positive but insignificant effect on MSME performance.These findings indicate that improving financial literacy is a crucial factor in enhancing MSME performance, while the implementation of E-Commerce and HR development still require further training and support. The results are expected to serve as a reference for local governments, training institutions, and MSME actors in formulating strategies to strengthen MSME competitiveness in the digital era.